1998
DOI: 10.1016/s0022-5347(01)62543-6
|View full text |Cite
|
Sign up to set email alerts
|

Radical Prostatectomy for Prostate Cancer: The Perineal Approach Increases the Risk of Surgically Induced Positive Margins and Capsular Incisions

Abstract: Although overall positive margins and biochemical failure rates are similar or identical for the perineal and retropubic approaches for organ confined prostate cancer, the perineal approach is associated with a significantly higher risk of capsular incisions and surgically induced positive margins and, thus, a higher risk of biochemical failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
8

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 12 publications
3
29
1
8
Order By: Relevance
“…Earlier studies have reported variable frequencies for the occurrence of CI. [13][14][15][16][17] The disparity may be attributable to differences in surgical technique, definition of CI, the characteristics of the patients studied and the stringency of the pathological analysis. Although the perineal approach has been reported to be more likely than the retropubic approach, to lead to CI with the risk of positive surgical margins in organ-confined tumors because of a limited surgical field, 17 RPP had pathological results, such as positive surgical margins and CI, similar to retropubic procedures with proper patient selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have reported variable frequencies for the occurrence of CI. [13][14][15][16][17] The disparity may be attributable to differences in surgical technique, definition of CI, the characteristics of the patients studied and the stringency of the pathological analysis. Although the perineal approach has been reported to be more likely than the retropubic approach, to lead to CI with the risk of positive surgical margins in organ-confined tumors because of a limited surgical field, 17 RPP had pathological results, such as positive surgical margins and CI, similar to retropubic procedures with proper patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] The disparity may be attributable to differences in surgical technique, definition of CI, the characteristics of the patients studied and the stringency of the pathological analysis. Although the perineal approach has been reported to be more likely than the retropubic approach, to lead to CI with the risk of positive surgical margins in organ-confined tumors because of a limited surgical field, 17 RPP had pathological results, such as positive surgical margins and CI, similar to retropubic procedures with proper patient selection. 4 Although an earlier study reported that the anterior prostate was the most common site for surgical margins with the perineal approach, 3 our results showed that positive surgical margins in the anterior prostate were present in six cases (2.2%), including three with organconfined cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous studies have addressed the issue of positive apical margins in RPP patients, this study is the first to compare apical margin status directly with apical soft tissue biopsies in RPP. 1,3,11 The two main findings of our study are that apical margin and apical soft tissue status are poorly correlated and that apical soft tissue status predicts biochemical failure whereas apical surgical margin status does not.…”
Section: Discussionmentioning
confidence: 73%
“…We present here a prospective assessment of the prognostic significance of apical surgical margins and soft tissue biopsies in patients with documented apical prostate cancer (PCA). 3,11 …”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported about the incidence of bladder neck or apical soft-tissue margins in relation to surgical technique of radical prostatectomy. [48][49][50][51][52] Djavan et al 53 were among the first to report the need of redefining PSA nadir after radical prostatectomy due to the finding of benign positive surgical margins after radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%